Pengaruh E-Samsat Dan Samkel Terhadap Kepatuhan Wajib Pajak Kendaraan Bermotor di Kota Sukabumi: Studi Kasus Pada UPTD Pusat Pengelolaan Pendapatan Daerah Wilayah Kota Sukabumi - Risma Dianti Putri; Venita Sofiani; Hendra Tanjung (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
This study aims to determine whether there is an effect of E-Samsat and Mobile Samsat on compliance of motor vehicle taxpayers in Sukabumi City. The method used is quantitative method with descriptive research type. The sample in this study were 100 motor vehicle taxpayers registered with the UPTD Pusat Pengelolaan Pendapatan Daerah Wilayah Kota Sukabumi using nonprobability sampling techniques. The data collection technique used a questionnaire using a 1-5 Likert scale instrument that had been tested for validity and reliability. Data processing using microsoft office excel and SPSS version 25 program then the data is analyzed by descriptive statistical test, instrument test, classical assumption test, partial test (t-test), simultaneous test (F-test), and determinant coefficient test (R2). The data analysis technique used to answer the hypothesis is multiple linear regression with the help of SPSS version 25. Based on the results of the simultaneous hypothesis test (F-test), it shows that the proposed hypothesis is accepted because it shows positive and significant hypothesis test results. This means that E-Samsat and Mobile Samsat have an effect on motor vehicle taxpayer compliance. The results of partial hypothesis testing (t-test) show that E-Samsat has an effect on motor vehicle taxpayer compliance. while Mobile Samsat has no effect on motorized vehicle taxpayer compliance.